Research Progress and Model Construction for Online Health Information Seeking Behavior - Liu, Zhi-Wei (Frontiers in Research Metrics and Analytics, 2022)
Under the background of COVID-19, online health information seeking has become one of the most important information needs of the public and even the only channel for health information seeking in this special period. A review of the research on online health information seeking behavior will help give full play to the previous academic research, further emphasize the necessity of Online health information seeking research and promote the development of research in this field. This study firstly presents the research overview of online health information seeking behavior by using the informetric method. Secondly, an overview is carried out from the perspective of online health information platform, group, quality, satisfaction, etc., to explore the influencing factors and their relationships in the process of online health information seeking. On this basis, the existing behavioral models are integrated and sorted out to build a new behavioral theoretical model in line with the current online health information seeking.